KARAKTERISTIK PETANI DAN KERAGAAN USAHATANI JAGUNG (Zea mays) LAHAN KERING BERIKLIM KERING (LKBK) DI KECAMATAN PRINGGABAYA - Muhammad Anwar; Rini Endang Prasetyowati (LPPM Universitas Gunung Rinjani, 2021)
The corn commodity can grow in various agricultural agro-ecosystems, one of which is dry land with a dry climate. Pringgebaya Subdistrict has the potential for dry land with a dry climate reaching 6,624 ha (23.50 percent) of the total dry land area in East Lombok Regency. This study aims to determine the description of the characteristics of farmers and the performance of corn farming. Dry land with dry climate in Pringgebaya District, East Lombok Regency. The method used is a descriptive survey. Determination of the research location using purposive sampling technique on farmers who are trying to plant corn in dry climate dry land in Pringgabaya District of East Lombok Regency. The number of respondents was determined by quota sampling, namely 40 respondents, then the selection of respondents used accidental sampling techniques. Additional data related to descriptions, technology packages and management of dry land farming with dry climates were obtained from key informants from the Field Officer of Pringgebaya Integrated Agricultural Service Unit. The farm data used are the planting season data for 2019/2020. Characteristics of the age of farmers are mostly at the productive age (87,5%) with the age range of 25 - 62 years, the level of formal education is dominated by junior high school education (40%), the number of family dependents is < 4 people (77.5%) with the category of small dependents, broad arable land at medium scale is 0.5-1 hectare per person (47.5%). The use of labor that is poured into corn farming in dry land with dry climates of Pringgebaya District is an average of 40-55 HOK / ha of Rp. 3,160,000 (42.5%) dominated by female agricultural workers / laborers. The use of fertilizer and pesticide production factors is 26.1% (Rp. 1,936,070) The use of production factors (irrigation, land rent, depreciation of agricultural machinery, and taxes) is 18.3% (Rp. 1,360,000).